THE NEW SPECTROPHOTOMETRIC STAR CATALOGUE - Komarov, N. S.; Arkhipov, M. G.; Basak, N. Yu.; Belik, S. I.; Cherkass, A. G.; Chuprina, R. I.; Depenchuk, E A.; Dragunova, A. V.; Dulapchi, I. F.; Gorbaneva, T. I.; Karamysh, V. F.; Kantsen, L. E.; et al. (Одеські астрономічні публікації, 2017)
The new spectral energy distributions Eλ for 360 stars in wavelength region from λ 330 to λ 725 nm are given. The observations for "relatively-absolute" stellar spectrophotometry were obtained at high-altitude astronomical station “Terskol” of Odessa Astronomical Observatory in 1973-1988 years. The station was located at a height of 3100 m in the Caucasus. The method of "relatively-absolute" spectrophotometry was used to obtain the spectral energy distribution. The comparison stars were α Lyr, β Ari, γ Ori, α Leo, ηUMa, α Aql, α Peg, β CMi, θ Leo and α Oph. The Eλ of all stars of comparison were reduced to α Lyr (except βCMi and θ Leo — their spectral distribution was reduced to stars βAri and α Leo respectively). The analysis of various mistakes was made and these were taken into account. The comparison with other Catalogues of the former USSR was made. It should be noted that the technique of observing and obtaining was unified. Similar optical and mechanical systems were used as well as analogous procedures of observations of stellar radiation and subsequent calculations. Only the register electronic devices were modified. The random errors of results for all the Catalogues are nearly equal 2 ÷ 3 % (to 5%) in the visual range of a spectrum and 5 ÷10% at the edges of the observed spectral bands – ultraviolet and near infrared regions. However, the random errors of spectrophotometry results of various authors have large discrepancies (up to several dozens (!) of percents sometimes).